Stenotrophomonas maltophilia Infections in Pediatric Patients – Experience at a European Center for Pediatric Hematology and Oncology - Zöllner, Stefan K.; Kampmeier, Stefanie; Froböse, Neele J.; Herbrüggen, Heidrun; Masjosthusmann, Katja; van den Heuvel, Alijda; Reicherts, Christian; Ranft, Andreas; Groll, Andreas H. (Frontiers in Oncology, 2021)
Stenotrophomonas maltophilia is an important nosocomial pathogen in immunocom-promised individuals and characterized by intrinsic resistance to broad-spectrum antibacterial agents. Limited data exists on its clinical relevance in pediatric patients with hematological or oncological disorders. In a retrospective single center cohort study in pediatric patients receiving care at the Pediatric Hematology and Oncology department, ten cases of invasive S.maltophilia infections (blood stream infections (BSI), 4; BSI and pneumonia, 3 or soft tissue infection, 2 ; and pneumonia, 1) were identified between 2010 and 2020. Seven patients had lymphoblastic leukemia and/or were post allogeneic hematopoietic cell transplantation (HCT). Invasive S.maltophilia infections occurred in a setting of indwelling central venous catheters, granulocytopenia, defective mucocutaneous barriers, treatment with broad-spectrum antibacterial agents, and admission to the intensive care unit. Whole genome sequencing (WGS) based typing revealed no genetic relationship among four individual S.maltophilia isolates. The case fatality rate and mortality at 100 days post diagnosis were 40 and 50%, respectively, and three patients died from pulmonary hemorrhage. Invasive S.maltophilia infections are an emerging cause of infectious morbidity in patients receiving care at the Pediatric Hematology and Oncology department.and carry a high case fatality rate.